Bupivacaine Mandibular Nerve Block Affects Intraoperative Blood Pressure and Heart Rate in a Yucatan Miniature Swine Mandibular Condylectomy Model: A Pilot Study. (1st February 2015) - Bova, Jonathan F.; da Cunha, Anderson F.; Stout, Rhett W.; Bhumiratana, Sarindr; Alfi, David M.; Eisig, Sidney B.; Vunjak-Novakovic, Gordana; Lopez, Mandi J.
ABSTRACT Purpose/Aim: The primary objective was to evaluate the effect of a bupivacaine mandibular nerve block on intraoperative blood pressure (BP) and heart rate (HR) in response to surgical stimulation and the need for systemic analgesics postoperatively. We hypothesized that a mandibular nerve block would decrease the need for systemic analgesics both intraoperatively and postoperatively. Materials and Methods: Fourteen adult male Yucatan pigs were purchased. Pigs were chemically restrained with ketamine, midazolam, and dexmedetomidine and anesthesia was maintained with isoflurane inhalant anesthesia. Pigs were randomized to receive a mandibular block with either bupivacaine (bupivacaine group) or saline (control group). A nerve stimulator was used for administration of the block with observation of masseter muscle twitch to indicate the injection site. Invasive BP and HR were measured with the aid of an arterial catheter in eight pigs. A rescue analgesic protocol consisting of fentanyl and lidocaine was administered if HR or BP values increased 20% from baseline. Postoperative pain was quantified with a customized ethogram. HR and BP were evaluated at base line, pre-rescue, 10 and 20 min post-rescue. Results: Pre-rescue mean BP was significantly increased (p = .001) for the bupivacaine group. Mean intraoperative HR was significantly lower (p = .044) in the bupivacaine versus saline group. All other parameters were not significant. Conclusion: Addition of a mandibular nerve block to the anesthetic regimen in the miniature pig condylectomy model may improve variations in intraoperative BP and HR. This study establishes the foundation for future studies with larger animal numbers to confirm these preliminary findings.